PERLINDUNGAN KONSUMEN PADA TRANSAKSI E-COMMERCE - Daniel Roni Tua (2021)
Trade activities in this era of globalization are growing very rapidly. One of the most influential factors is the advancement of information technology. Advances in information technology and trade activities are advancing in tandem so that a facility called e-commerceis formed. E-commerce facilities greatly facilitate business actors and consumers in transacting. But behind all the facilities available, there are many negative things that will unconsciously attack e-commerce consumers if they don't understand what protection they have. This writing is done to find out about consumer protection against e-commerce transactions regarding the responsibility of e-commerce business actors if consumers experience losses. This research is a normative juridical type using secondary data collected through library research. From this research, it can be concluded that e-commerce consumers have legal protection rights based on the law. Therefore, e-commerce business actors must be aware so that there is no fraud or loss that occurs.